Jaw Exercise Therapy and Psychoeducation to Reduce Oral Parafunctional Activities for the Management of Persistent Dentoalveolar Pain - Izumi Makino; Young-Chang Arai; Shuichi Aono; Masayuki Inoue; Hiroki Sakurai; Yusuke Ohmichi; Kazuhiro Shimo; Makoto Nishihara; Jun Sato; Noboru Hatakeyama; Takako Matsubara; Tatsunori Ikemoto; et al. (Pain Research and Management)
Objective. To retrospectively analyze the effects of our original combination therapy treatment on patients with nonodontogenic persistent dentoalveolar pain. Methods. Twenty-one patients suffering from persistent dentoalveolar pain (nineteen females and two males; mean age ± standard deviation: 55.7 ± 19.6 years) participated in this study. They were treated with a therapy combination of jaw exercise and psychoeducation to reduce oral parafunctional activities every month. The intensity of pain in these subjects was evaluated using a numerical rating scale (NRS) before and after treatment. Results. The NRSs at the baseline ranged from 5 to 10 (median, 8), from 0 to 10 (median, 2) at one month after treatment, from 0 to 10 (median, 1) at three months after treatment, and from 0 to 10 (median, 0) at the end of treatment. Pain intensity after treatment improved significantly. Conclusion. There was a significant reduction in pain after our combination of therapies as nonpharmacological treatments, and therefore this treatment could be useful in the management of NPDP patients.